The effects of low-molecular-weight heparin at two different dosages on thrombin generation in cancer patients. - Traby, Ludwig; Kaider, Alexandra; Schmid, Rainer; Kranz, Alexander; Quehenberger, Peter; Kyrle, Paul A.; Eichinger, Sabine (Thrombosis and Haemostasis, 2010)
Non-surgical cancer patients are at high thrombotic risk. We hypothesised that the prothrombotic state is reflected by elevated thrombin generation and can be mitigated by increasing the low-molecularweight heparin (LMWH) dose. Non-surgical cancer patients were randomised to enoxaparin 40 or 80 mg. D-dimer, prothrombin fragment F1+2 (F1+2) and peak thrombin (PT) were measured 2, 4, 6 hours (h) after LMWH (day 1) and daily for 4 days. A total of 22 and 27 patients received enoxaparin 40 and 80 mg, respectively. D-dimer and F1+2 moderately decreased after 6 h in both groups. After enoxaparin 80 mg, D-dimer baseline levels [median (quartiles)] decreased from day 1 to 4 [1054.9 (549.5, 2714.0) vs. 613.0 (441.1, 1793.5) ng/ml] (p<0.0001), while no difference was seen after 40 mg. Baseline PT levels [median (quartiles)] were 426.2 nM (347.3, 542.3) (40 mg) and 394.0 nM (357.1, 448.8) (80 mg). After 80 mg, PT significantly decreased to 112.4 nM (68.5, 202.4), 57.1 nM (38.0, 101.2) and 43.6 nM (23.4, 112.8) after 2, 4 and 6 h, which was lower than after 40 mg (p=0.003). After 80 mg, PT decreased from day 1 to 4 [358.6 nM (194.2, 436.6); p=0.06] while no difference was seen after 40 mg. In conclusion, in cancer patients coagulation activation and thrombin generation is substantially increased. Peak thrombin levels are sensitive to the anticoagulant effects of LMWH at different dosages. The prothrombotic state is substantially attenuated by higher LMWH doses.
Keywords: Venous thrombosis; thrombin; cancer; prophylaxis; heparins; LMWH